PENGARUH Trichoderma sp. TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAWAWUT (Setaria italica L. Beauv) PADA KONDISI CEKAMAN KEKERINGAN - Dewi, Sheli Mustikasari; Amalia, Istia Siti; Ningtyas, Dewi Nurma Yanti; Haqia, Thoriq Muhammad; Yusuf, Muhammad (Jurnal Agroteknologi, 2026)
Drought stress caused by limited water supply in the root zone can inhibit plant growth. Foxtail millet (Setaria italica L. Beauv) is an alternative carbohydrate source known for its drought tolerance and ease of cultivation. Biofertilizers based on Trichoderma sp. can serve as biological agents that promote plant growth under abiotic stress conditions, including drought. This study aimed to evaluate the effect of Trichoderma sp. application on growth and yield of foxtail millet under drought stress conditions. This study was conducted at the Munjuljaya Experimental Field, Purwakarta Regency, using a factorial Randomized Block Design (RBD) with three replications. The first factor was Trichoderma sp. dosage with four levels: T0 (0 g), T1 (20 g), T2 (40 g), and T3 (60 g). The second factor was drought stress with three levels: C1 (25% field capacity), C2 (50% field capacity), and C3 (75% field capacity). In total, 30 experimental units were tested. The results showed that Trichoderma sp. application and water treatment did not significantly affect plant height, tiller number, leaf chlorophyll index, panicle length, panicle weight, fresh root weight, root length, 1000-seed weight, and shoot-root ratio. However, the highest dosage of Trichoderma sp. improved several growth parameters, such as plant height in T3 (60 g) with 78.13 cm, panicle length in T3 (60 g) with 8.77 cm, fresh root weight at 81 DAP (days after planting) in T3 (60 g) with 6.88 g, and the highest shoot-root ratio in T3 (60 g) with 3.35. This study has an impact on the growth and yield of millet because Trichoderma sp. plays a role in root growth and plant nutrient absorption.